1999
DOI: 10.1001/archinte.159.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Hypoglycemic Coma in 102 Diabetic Patients

Abstract: Hypoglycemic coma is a serious and not an uncommon problem among elderly patients with diabetes mellitus and treated with insulin and/or oral hypoglycemic drugs. Risk factors contribute substantially to the morbidity and mortality of patients with drug-induced hypoglycemic coma. Enhanced therapeutic monitoring may be warranted when hypoglycemic drugs are administered to an elderly patient with the above predisposing factors and potentiating drugs for hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(120 citation statements)
references
References 45 publications
1
116
0
3
Order By: Relevance
“…Second, physicians often perceive hyperglycemia as a consequence of stress and acute illness and often delay treatment until blood glucose levels exceed 200 mg/dl (2,21). Third, fear of hypoglycemia constitutes a major barrier to efforts to improve glycemic control, especially in patients with poor caloric intake (5,22). Finally, physicians frequently hold their patient's previous outpatient antidiabetes regimen and initiate sliding-scale coverage with regular insulin, a practice associated with limited therapeutic success and suboptimal glycemic control (16,17,23,24).…”
Section: B Sliding Scale Regimen With Regular Insulinmentioning
confidence: 99%
“…Second, physicians often perceive hyperglycemia as a consequence of stress and acute illness and often delay treatment until blood glucose levels exceed 200 mg/dl (2,21). Third, fear of hypoglycemia constitutes a major barrier to efforts to improve glycemic control, especially in patients with poor caloric intake (5,22). Finally, physicians frequently hold their patient's previous outpatient antidiabetes regimen and initiate sliding-scale coverage with regular insulin, a practice associated with limited therapeutic success and suboptimal glycemic control (16,17,23,24).…”
Section: B Sliding Scale Regimen With Regular Insulinmentioning
confidence: 99%
“…Furthermore, the incidence of adverse events in renally impaired patients who received repaglinide was comparable to that in patients with normal renal function. These are important endorsements of the safety of this agent in a group of patients who are often in need of enhanced metabolic control but who are also often at risk for hypoglycemia due to (often unknown) renal impairment on the other side (14).…”
Section: Conclusion -No Relationshipmentioning
confidence: 99%
“…Death occur in 5 patients(4.9%). 70 A prospective one year study found sixty five of 125 (52%) admissions for hypoglycemia presented with obtundation, stupor or coma. 29 While the length of time in coma could not always be determined, the one death related to hypoglycemia occurred in a patient with coma lasting over 20 hours.…”
Section: Hypoglycemic Comamentioning
confidence: 99%